Rancang Bangun Mesin Distilasi Minyak Atsiri dengan Sistem Pendingin Kontinu sebagai Sarana Praktikum dan Produksi Essential Oil di Laboratorium Rekayasa Pangan - Ikhwanudin, Angga Herviona; Widadi, Nurul; Guntoro; Abidin, Ahmad Zainal; Oktanuriawan, Jefry (Jurnal Pengelolaan Laboratorium, 2025)
An essential oil distillator consists of a distillation kettle, condenser, cooling water tank, and separating funnel. The design of this tool aims to create an essential oil distillation machine that can be used as a learning tool in practicums, research and community service. The research method used is research and development consisting of design, manufacture, testing of tool performance and testing of essential oil quality. The essential oil distillation procedure in this study is the steam method. The materials used are eucalyptus leaves and twigs, citronella leaves, and kaffir lime leaves and twigs. The performance testing of the tool carried out consists of distillation rate, essential oil yield, distillation process temperature, physical properties of materials, fuel consumption, cooling water performance, and fuel consumption efficiency. Testing of the quality of the essential oil produced consists of odor, color, refractive index, specific gravity, and substance content tests through GCMS tests. This tool was successfully made and produced eucalyptus, citronella, and kaffir lime essential oils. The yield of essential oil of citronella leaves was 0.208%, eucalyptus leaves 0.37%, and kaffir lime leaves 0.575%. Meanwhile, the test results for the specific gravity of essential oil of citronella leaves were 0.8712, eucalyptus leaves 0.9130, and kaffir lime leaves 0.8528. The test results for the refractive index of essential oil of citronella leaves were 1.475, eucalyptus leaves 1.489, and kaffir lime leaves 1.448. The distillation rate of essential oils produced was 0.00249 kg/hour (eucalyptus leaves), 0.00272 kg/hour (lemongrass leaves), and 0.00828 kg/hour (kaffir lime leaves). The average energy efficiency of the distillation equipment produced was 48.79%.